Service Design in Tourism: Tourist Experience Driven Destination in Qingzhou Ancient City, China - Yuliang, He (UNIVERSITI MALAYSIA SARAWAK, 2024)
The study found a significant gap between tourists' perceptions and expectations of service quality in Qingzhou Ancient City, with notable differences across various dimensions of service quality. It also identified the factors influencing the service quality of Qingzhou Ancient City tourism services. Four critical incidents were identified, highlighting areas for improvement and optimization. Additionally, the study uncovered opportunities for service design within Qingzhou’s tourism services. Based on these findings, the researcher proposes a practical service design strategy framework to help destination managers enhance tourist experiences and foster value co-creation with stakeholders. This study explored factors influencing tourists' perceived service quality in Qingzhou Ancient City, a renowned historical and cultural destination in China. The researcher employed a mixed-methods approach tailored to specific research questions. The researcher used a quantitative method for the first question involving questionnaire surveys. To address the second question, the researcher used a multi-step qualitative method, including personas, observations, guided interviews, service safaris, and customer journey maps. These tools are integral to service design. For the third question, the researcher combined qualitative methods, such as observation and interviews, with service blueprint and customer journey map methodologies. The study significantly contributes to the theoretical advancement of tourism destination service design, particularly for ancient city destinations. The researcher developed a model for assessing tourism service quality and a strategic framework for service design in Qingzhou Ancient City, enhancing the application of service design principles. Using customer journey maps improved the clarity and executability of service management. The service design process, rooted in a shared service concept, enhances Qingzhou’s competitiveness. Key touchpoints in the Customer Journey Map facilitate consistent stakeholder goals, empowering Destination Marketing Organizations (DMOs) to create innovative, visitor-centric solutions. The service design strategy framework helps providers pinpoint their roles and potential partners, optimizing operations and collaboration. Future research should refine the service design framework for various destinations and explore how emerging technologies can enhance tourism experiences and service design methodologies. Investigating the integration of infrastructure with new technologies and the impact of tourism on ecosystems will further contribute to sustainable tourism development.